Reduction of Workforce due to Impact of Covid-19 and Occupational Health and Safety Management at Workplace - Dubey, Praveen; Singh, Garima; Nagaraju, G.; Gharat, Kailash; Bharambe, S. D.; Vajarekar, Anant (International Journal of Occupational Safety and Health, 2020)
COVID-19 pandemic has led to health crisis as well as slowdown of industrial activities throughout the world resulted in global economic loss. Safety measure of social distancing by workers at workplaces to prevent spread of corona virus leads to huge losses especially in the service sector jobs that depend on customer-provider interactions or involve the congregation of large number of people. Also, the process equipment and machinery may not function smoothly or will be unavailable as these are under continuous shut down during the lockdown period. As workplaces have been forced to cut down their expenditure and recheck their workforce to maintain social distancing, workers in industries are at a higher risk of losing their jobs. Fewer workforces at workplace have increased workload on available workers along with fear of insecurity due to pandemic. Under these circumstances, the responsibility of the management is to keep balance between production, profit and safety at workplace as well as to keep employees motivated and free from the stressful environment due to pandemic. This paper addresses the challenges and the methods to prevent and mitigate occurring of accidents at workplaces which are having reduced workforce and malfunctioning of equipment and machinery as compared to pre-COVID 19 scenarios.